(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Transitional cell carcinomas (TCC) of the bladder are a major health problem and can be a leading cause of death. There are several proteolytic enzymes which are responsible for the degradation of the extra cellular components and have an essential role in tumor invasion and metastasis. MMP-2 and MMP-9 are the most important class of these enzymes. Objective:To assess the In situ hybridization expression of MMP-2 and MMP-9 in TCC of the bladder. Methods: Fifty formalin fixed, paraffin embedded of TCC of the bladder tissue blocks from Specialized Surgical Hospital in Baghdad, were included in this study. In addition ten apparently normal bladder autopsies were collected from the Forensic Medicine Institute Archives used as control group. Tissue blocks were sectioned on charged slides to be used for In situ hybridization, for the detection of MMP-2 and MMP-9. Results:The expression of MMP-2 and MMP-9 in TCC of the bladder tissues in the present study was 64 % for both and strong relationship between expression of MMP-2 and MMP-9 and TCC of the bladder was detected. Conclusion: MMP-2 and MMP-9 play an important role in progression of transitional cell carcinoma of the bladder. Key words:Bladder cancer, Matrix Metalloproteinases, invasion, metastasis, carcinogenesis.